Response of three maize varieties (Zea mays L.) to different nitrogen dosages. Issue 4 (July 2021) - Riadi, M; Amin, A R; Novianti, F; Musa, Y; Farid, M; Dungga, N E; Sahur, A
Abstract: The research was carried out at the Experimental Garden of the Cereal Research Institute, Bajeng District, Gowa Regency, South Sulawesi Province, which took place from September 2018 to January 2019. The research aimed to study the interaction between certain nitrogen doses and certain maize varieties and the presence of maize varieties, as well as nitrogen doses provide the highest growth and production. This research was conducted in the form of an experiment using a separate plot design. The nitrogen dose as the main plot consisting of 4 levels, namely urea 0 kg.ha −1, 100 kg.ha −1, 200 kg.ha −1, and 300 kg.ha −1, then three varieties of maize as subplots, namely Bima-19 variety as hybrid representative, Lamuru as composite representative, and Srikandi Kuning as synthetic representative. The results showed that the Bima-19 variety fertilized with urea 300 kg.ha −1 gave the highest seed yield per hectare (8.10 tons.ha −1 ), and the Srikandi Kuning variety produced the highest ear height (91.25 cm) compared to other varieties tested. Application of urea 300 kg.ha −1 resulted in the highest ear height (113.19 cm), the longest ear length (20.02 cm), and the highest number of seeds. 33.83 seeds). All parameters observed had very significant positive correlation values, except for the age of flowering of the females and the number of seed rows of cob −1 which were significantly positive.